Pembuatan Spanduk Promosi dan Pemanfaatan WhatsApp Business pada UMKM Dimsum Cukikana Parongpong - Kristalia Vitaloka; Grace Orlyn Sitompul; Cynthia Laura Silalahi; Irfan Pandang Lumban Tobing (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face serious challenges in marketing and operational management in the digital age. Dimsum Cukikana, a culinary business located in Parongpong, West Bandung Regency, faces similar issues, namely unstructured order management due to the use of personal WhatsApp accounts mixed with personal conversations, the lack of a digital product catalog, and a scarcity of physical promotional materials capable of attracting potential customers in the vicinity of the business. These conditions have resulted in low business visibility and inefficient customer service processes. This community service initiative aims to improve the effectiveness of Dimsum Cukikana’s promotions and order management through the implementation of WhatsApp Business and the provision of promotional banners. The implementation method was carried out in stages, including field studies and in-depth interviews with the business owner to identify needs, followed by the application of digital solutions such as creating a WhatsApp Business account, setting up a product catalog and automated messaging features, as well as the creation and installation of promotional banners. The analysis technique used was qualitative descriptive analysis based on direct observations and a comparison of conditions before and after the implementation of the solutions. The results of the initiative show that using WhatsApp Business successfully separates business communications from personal accounts, makes it easier for customers to access menu and pricing information via the catalog feature, and streamlines the ordering process. The installation of promotional banners featuring signature menu items and the WhatsApp Business number increased the business’s visibility and made it easier for potential customers to get in touch. During the observation period, there was a 10% daily increase in the number of customers placing orders via WhatsApp Business.